2013
DOI: 10.1016/j.jvs.2012.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Experience with a new negative pressure incision management system in prevention of groin wound infection in vascular surgery patients

Abstract: In this clinical study, Prevena negative pressure dressing significantly decreased the incidence of groin wound infection in patients after vascular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(146 citation statements)
references
References 12 publications
5
139
0
2
Order By: Relevance
“…It delivers intermittent or continuous negative pressure (ranging from <50mmHg to >125mmHg) to the wound site which is covered with a foam or gauze dressing and sealed with an occlusive drape. Success has been reported in complex wounds 35 with emerging evidence to show that its use in high risk, post-operative incisions prevents SSIs [36][37][38][39][40] . The likely modes of action are through holding wound edges together (thereby reducing the likelihood of surgical dehiscence), stimulation of perfusion, reduction of lateral tension, haematoma and oedema, and protection of the surgical site from exogenous sources of micro-organisms.…”
Section: Negative Pressure Wound Therapy (Npwt)mentioning
confidence: 99%
“…It delivers intermittent or continuous negative pressure (ranging from <50mmHg to >125mmHg) to the wound site which is covered with a foam or gauze dressing and sealed with an occlusive drape. Success has been reported in complex wounds 35 with emerging evidence to show that its use in high risk, post-operative incisions prevents SSIs [36][37][38][39][40] . The likely modes of action are through holding wound edges together (thereby reducing the likelihood of surgical dehiscence), stimulation of perfusion, reduction of lateral tension, haematoma and oedema, and protection of the surgical site from exogenous sources of micro-organisms.…”
Section: Negative Pressure Wound Therapy (Npwt)mentioning
confidence: 99%
“…And finally, other technologies can be useful to decrease the postoperative complications of femoral approaches. Svensson et al 38 demonstrated the utility of the VAC system for the healing of infected femoral approaches, and Matatov et al 39 decreased from 30% to 6% the rate of infection after femoral approach thanks to the use of an aspirated wound dressing system (Prevena).…”
Section: Discussionmentioning
confidence: 99%
“…Aus den uns vorliegenden Daten kann jedoch noch keine verlässliche Interpretation abgeleitet werden. Die Wirksamkeit der präventiven Unterdrucktherapie wurde hingegen bereits in einigen Studien verschiedener chirurgischer Fachgebiete wie der Herz-und Thoraxchirurgie [9,13,14], Orthopädie und Unfallchirurgie [10,23,24], Gefäßchirurgie [25] und plastischen Chirurgie [15,26] untersucht (l " Tab. 2).…”
Section: Material/methodenunclassified